2017
DOI: 10.11648/j.jfmhc.20170301.15
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and Health Care Practice of Mothers’ About Obstetric Danger Signs at Haramaya District, Eastern Ethiopia

Abstract: Abstract:Mother's awareness of potential obstetric danger signs during pregnancy, child birth and immediate post-delivery are crucial to influence their decisions to seek immediate health care. However, their awareness and health care practice were not well known in Haramaya district. Thus, this study was to assess mother's awareness of obstetric danger signs and their health care seeking practice. Community based cross sectional study was conducted in June, 2012 on 757 mothers who gave birth for the last two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
2
2
1
Order By: Relevance
“…Mothers who had primary, secondary, and above educational levels were 4.85 and 6.90 times more likely to have good knowledge of the danger signs of pregnancy. This finding is consistent with other studies conducted in different parts of Ethiopia and other countries 7 , 9 , 12 , 16 , 21 , 27 , 39 , 48 , 51 – 53 . Education gives the impression to play a positive role in increasing the knowledge of women about danger signs during pregnancy and its complications 54 .…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Mothers who had primary, secondary, and above educational levels were 4.85 and 6.90 times more likely to have good knowledge of the danger signs of pregnancy. This finding is consistent with other studies conducted in different parts of Ethiopia and other countries 7 , 9 , 12 , 16 , 21 , 27 , 39 , 48 , 51 – 53 . Education gives the impression to play a positive role in increasing the knowledge of women about danger signs during pregnancy and its complications 54 .…”
Section: Discussionsupporting
confidence: 93%
“…While less than one-third of the pregnant women identified abnormal body movement (30.90%), abnormal vaginal discharge (29.20%), the difficulty of breathing (28.70%), and loss of consciousness (25.40%) as the danger signs of pregnancy. This finding is consistent with other studies conducted in different parts of Ethiopia and other countries 7 , 9 11 , 13 , 17 , 40 , 47 . This indicates that more than half of pregnant women may know at least one or more danger signs of pregnancy, while the remaining even may not be known one danger sign of pregnancy.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This finding is supported by previous research in Ethiopia showing that bleeding during childbirth is one of the most commonly known danger signs amongst community members. [25][26][27] The existing concern for the gravity of PPH will likely improve acceptability of an innovation for PPH prevention, as previous reviews have shown that adoption of a novel product or program is facilitated if it addresses an issue that is experienced or prioritised by adopting stakeholders. 28,29 Further, amongst healthcare providers, there was a recognition that oxytocin is the gold standard drug for PPH prevention, thus an inhaled oxytocin product may be acceptable to these stakeholders when compared to a completely novel drug molecule.…”
Section: Discussionmentioning
confidence: 99%